TINJAUAN SOSIAL YURIDIS TERHADAP PENGGUNA NARKOBA SEBAGAI ALASAN PERCERAIAN DI PENGADILAN AGAMA BONE - Makkarateng, Ma'adul Yaqien (Institut Agama Islam Negeri Bone, 2021)
Describe research results that in deciding such cases, judges trying to objectively and take the liver carefully because it is not a little too case arising not from the pure drug factor, but from other elements such as economic problems, passive communication, infidelity, even domestic violence drug items, which renders as an additional reason for filing the lawsuit in the divorce. The judge's ruling on a lawsuit containing divorce domestic violence are less precise because there are drugs, because in article 116 compilation of Islamic law of the letter (f) stating that intoxicating items including drugs, although the case is not purely because of Drugs or other reasons that make drugs as the reason. From the discussion of the above research, advice given by the author are: Increased awareness between fellow in particular within the family, in a family affected by drugs, preferably a family member more attention so as not to extend to the other. Intensive healing process both in terms of religious or medical establishments that will really help healing drugs. For the Religious Court judge Grade 1 A Watampone should take careful and meticulous in deciding things that there are elements of drugs, both from examination to the use of the legal basis in deciding things that contain elements of drugs.